Speech and non-speech processing in people with specific language impairment: a behavioural and electrophysiological study. - McArthur, G; Bishop, D (2005)
McArthur and Bishop (2004) found that people with specific language impairment (SLI) up to 14 years of age have poor behavioural frequency discrimination (FD) thresholds for 25-ms pure tones, while people with SLI upto 20 years of age have abnormal auditory N1--P2--N2 event-related potential (ERP) responses to the same tones. In the present study, we extended these findings to more complex non-speech and speech sounds by comparing younger (around 13 years) and older (around 17 years) teenagers with SLI and controls for their behavioural FD thresholds and N1-P2 ERPs to 25 and 250-ms pure tones, vowels, and non-harmonic complex tones. We found that a subgroup of people with SLI had abnormal responses to tones and vowels at the level of behaviour and the brain, and that poor processing was associated with the spectral complexity of auditory stimuli rather than their phonetic significance. We suggest that both the age of listeners and the sensitivity of psychoacoustic tasks to age-related changes in auditory skills may be crucial factors in studies of sound processing in SLI.